Business process reengineering in increase brand awareness SKYZ card - Muchson, -; Sihwahjoeni, - (International Research Journal of Management, IT & Social Sciences, 2018)
Mandiri SKYZ card (travel card products) is a master card credit card rebranding titanium to facilitate customers who often abroad. This study aimed to analyze the effect of business process reengineering in the face of the offensive marketing to increase brand awareness SKYZ Card. The sample in this study as many as 100 people. The analysis technique used is simple regression analysis. The analysis showed that the business process reengineering significant effect on Brand Awareness SKYZ Card. This shows that the better Business process reengineering can improve brand awareness. Therefore, in the face of the offensive marketing need to design the look of the existing SKYZ Card website in order to become more attractive.